Rhino-ocular and rhino-oculo-cerebral mucormycosis; two extremes of clinical spectrum complicating COVID-19 disease: two case reports - Fotedar, Sanjay; Mahapatra, Sarthak; Supragya, Kunj (International Journal of Research in Medical Sciences, 2023)
Corona virus disease 2019 is associated with wide spectrum of clinical features and secondary events complicating the natural course of disease, including infectious and noninfectious complications. As pandemic is evolving wide range of secondary infections including bacterial and fungal infections complicating the clinical course of COVID-19 disease are being reported, authors report two cases of rhino-orbital and rhino-orbito-cerebral mucormycosis in a patient of COVID-19 pneumonia. Mucormycosis is caused by saprophytic fungi involving nasal passages, sinuses, oral cavity and brain commonly. It is usually seen immunocompromised host and in diabetics with poorly controlled blood sugar level at times normal host though rare. High index of clinical suspicion is needed to suspect and diagnose mucormycosis to maximize the survival as disease is highly fatal because of its angio-invasive pathology.